Factors Affecting Profitability: The Case of Coal Mining Sector Listed Firms in the Indonesia Stock Exchange (IDX) - Berlianti, Wahyuni; Fatimah, Fatimah; Junaidi, Junaidi (Training & Research Institute - Jeramba Ilmu Sukses (TRI-JIS), 2025)
This comprehensive study aims to determine the factors that affect profitability in coal mining companies listed on the Indonesia Stock Exchange (IDX). The data used in this study are secondary. The population in this study consists of coal mining companies listed on the Indonesia Stock Exchange, comprising 34 companies, of which 11 were selected as samples. The data collection technique used is the Library study technique. The research method used is quantitative research. The analysis model used in this study is descriptive. The results show that simultaneously, the current ratio, quick ratio, cash ratio, debt-to-assets ratio, and debt-to-equity ratio have a significant effect on profitability. To some extent, the current ratio has a positive impact on profitability. To some extent, the quick ratio has a positive impact on profitability. To some extent, the cash ratio has a positive impact on profitability. To some extent, the debt-to-assets ratio has a positive impact on profitability. Partially, the debt-to-equity ratio does not affect profitability